A exploração do trabalho infantil na região de Maringá e suas implicações jurídicas e sociais - Machado, Aparecido Silva (2015)
The protection of the rights of children and adolescents is related to human rights, as fundamental values of human dignity. It is a necessary condition for being inserted into a democratic state. Thus it is essential to eliminate any kind of exploitation of child labor. It is from this issue we set out to develop this work. It analyzed the exploitation of child labor from the perspective of their occurrence in the State of Paraná, especially in the metropolitan region of Maringá. It is important to be noted that the child needs to fully develop their physical and mental aspect. And for that to happen there must be appropriate conditions. The situation of poverty has damaged considerably the scope of the objective which is to make these children and adolescents citizens. His labor has been exploited for centuries around the world. The Brazil, the State of Paraná and the region of Maringá, albeit on a smaller scale has been no different. This makes us question the causes and consequences of this exploitation. The key issue is to give effect to the existing rules, in accordance with public policy and government social programs. For this to happen it is important the participation of the family, society and government agencies. Only with constant action that will be overcome